The Relationship between Autonomic Regulation of Cardiovascular Function and Body Composition - Tomislav Smoljo (Journal of Obesity & Metabolic Syndrome, 2020)
Background : We investigated whether the results of autonomic function tests correlate with body composition and shape in healthy young people. Methods : We conducted cardiovascular reflex tests (heart rate [HR] and blood pressure [BP] responses to the Valsalva maneuver and HR response to deep breathing) and the tilt table test with 32 subjects (19 males; mean age, 22.1±1.9 years). Participants also completed an anthropometric measurement sequence (weight; height; upper arm, hips, and waist circumference; triceps and subscapular skinfold), bioelectric impedance testing, and hand grip strength measurements. Results : Markers of obesity, other anthropometric measures, functional measures, and the basal metabolic rate (BMR) were significantly positively correlated with systolic BP (SBP) and diastolic BP (DBP) in both the supine and tilted positions. There was a positive correlation between the difference in HR (ΔHR) between the tilt and supine body positions and markers of obesity, the functional marker of dominant handgrip strength, and BMR. Participants with a body mass index (BMI) <25 kg/m² had significantly lower median values of ΔHR, DBP in the tilt-test, SBP at rest, and SBP in the tilt-test than participants who had a BMI ≥25 kg/m² (10.55 vs. 21.95 bpm, P=0.003; 77.55 vs. 90.05 mmHg, P=0.045; 113.45 vs. 140.55 mmHg, P=0.013; 117.00 vs. 135.25 mmHg, P=0.006, respectively). Body fat percentage was identified as an independent positive predictor (β=0.993; 95% confidence interval [CI], 0.070 to 1.916; P=0.036) and body water percentage was an independent negative predictor of tilted SBP (β=–1.370; 95% CI, –2.634 to 0.106; P=0.035). Conclusion : High sympathetic activity, as evaluated by cardiovascular regulation, correlates with a high share of adipose tissue in young healthy persons.